2016
DOI: 10.1002/ca.22767
|View full text |Cite
|
Sign up to set email alerts
|

The sulci of the inferior surface of the temporal lobe: An anatomical study

Abstract: Understanding the anatomy of temporal lobe sulci and their variations can allow for safer neurosurgical approaches. Although the inferior temporal sulci and their relations to each other has been described by several authors, the nomenclature used has not been universal. The aim of this study was to investigate the anatomic features of the three main sulci of the inferior temporal lobe and provide a simple description of complex patterns among these sulci. Sulcal variations and their relations were examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
6
1
Order By: Relevance
“…The inter-hemispheric correlation between types was high ( r = 0.71), meaning that both hemispheres of a same subject tended to share the same type. The differences in type proportions between the present study and previous studies were not significant using proportions z -tests: comparison between the present study with Ono et al (1990) : p = 0.16; with Novak et al (2002) : p = 0.86; with Kim et al (2008) : p = 0.40; with Huntgeburth and Petrides (2016) : p = 0.89; with Chau et al (2014) : p = 0.75; and with Cikla et al (2016) : p = 0.58. More details about comparison with previous studies are to be found in the Discussion section of this paper.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…The inter-hemispheric correlation between types was high ( r = 0.71), meaning that both hemispheres of a same subject tended to share the same type. The differences in type proportions between the present study and previous studies were not significant using proportions z -tests: comparison between the present study with Ono et al (1990) : p = 0.16; with Novak et al (2002) : p = 0.86; with Kim et al (2008) : p = 0.40; with Huntgeburth and Petrides (2016) : p = 0.89; with Chau et al (2014) : p = 0.75; and with Cikla et al (2016) : p = 0.58. More details about comparison with previous studies are to be found in the Discussion section of this paper.…”
Section: Resultscontrasting
confidence: 64%
“…Meanwhile, the complex sulcal pattern of the MTL defines a framework of anatomical landmarks to be used for locating the adjacent cortices ( Insausti et al, 1998 ; Huntgeburth and Petrides, 2012 ; Augustinack et al, 2013a ; Kivisaari et al, 2013 ). In fact, the rhinal sulcus (RS) and the collateral sulcus (CS) display various morphological conformations ( Ono et al, 1990 ; Kim et al, 2008 ; Feczko et al, 2009 ; Huntgeburth and Petrides, 2012 ; Cikla et al, 2016 ). One of the most visible sulcal variation in the MTL is that the RS and CS can be either connected or separated (at a level slightly caudal to the caudal tip of the entorhinal cortex), which may impact the boundary localization, and the volume, surface area and cortical thickness of the adjacent cortices ( Pruessner et al, 2002 ; Feczko et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous works relied on pattern-based classification, i.e. patterns comprising several sulci rather than individual connections were rated (Kim et al 2008;Cikla et al 2016;Ovalioglu et al 2018) Although the collateral sulcus (CS) has a very constant morphology in its anterior part, it can be present as a single-branch, separated into two branches (an occipital branch and a temporal branch), or can be composed of two non-connected sulci in its posterior part (Figure 2). This sulcus delimits the medial occipito-temporal gyrus (formed by the para/hippocampal gyrus in the anterior part and the lingual gyrus in the posterior part) from the lateral occipitotemporal gyrus, also called the fusiform gyrus (Figure 2).…”
Section: A Connection-based Classificationmentioning
confidence: 99%
“…Connection-based sulcal variations are mainly studied by neurosurgeons, especially in the medio-basal part of the temporal lobe, which is a path of surgical approach used to treat pathologies such as some tumors and arteriovenous malformations, or pharmaco-resistant temporal lobe epilepsy (Cikla et al 2016;Ovalioglu et al 2018). Several post mortem studies have focused on describing the sulci of the inferior surface of the temporal lobe (collateral, occipito-temporal, and rhinal), by measuring their length, depth and mutual connections using dissected brains (Cikla et al 2016;Ovalioglu et al 2018). Another study (Kim et al 2008), using MRI images, showed a possible link between temporal lobe epilepsy and the mutual connections of these sulci.…”
Section: Introductionmentioning
confidence: 99%
“…The occipitotemporal sulcus ( sulcus occipitotemporalis , also known as the lateral occipitotemporal sulcus) separates the medial part of the inferior temporal gyrus (T3 or gyrus temporalis inferior ) from T4. Various classifications for the temporal sulci and gyri have been published (Ono et al, 1990 ; Duvernoy, 1992 ; Hanke, 1997 ; Huntgeburth and Petrides, 2012 ; Chau et al, 2014 ; Cikla et al, 2016 ) with different relations between the collateral and rhinal sulci and patterns of the various sulci.…”
Section: Inferomedial Surface Of the Cerebral Hemispherementioning
confidence: 99%